Applications of thermal imaging in avian science. (6th December 2012) - McCafferty, Dominic J.; Marsden, Stuart
<x xml:space="preserve">Abstract</x> Thermal imaging, or infrared thermography, has been used in avian science since the 1960s. More than 30 species of birds, ranging in size from passerines to ratites, have been studied using this technology. The main strength of this technique is that it is a non‐invasive and non‐contact method of measuring surface temperature. Its limitations and measurement errors are well understood and suitable protocols have been developed for a variety of experimental settings. Thermal imaging has been used most successfully for research on the thermal physiology of captive species, including poultry. In comparison with work on mammals, thermal imaging has been less used for population counts, other than for some large bird species. However, more recently it has shown greater success for detection of flight paths and migration. The increasing availability and reduced cost of thermal imaging systems is likely to lead to further application of this technology in studies of avian welfare, disease monitoring, energetics, behaviour and population monitoring.